4th International Conference on Spoken Language Processing (ICSLP 1996) 1996
DOI: 10.21437/icslp.1996-408
|View full text |Cite
|
Sign up to set email alerts
|

Optopalatograph (OPG): a new apparatus for speech production analysis

Abstract: This paper describes the early development of a device for measuring tongue-palate distance, contact and pressure across the whole of the hard palate. The Optopalatograph (OPG) is similar in principle to the Glossometer and similar in configuration to the Electropalatograph. It uses optical fibres to relay light to and from the palate and distance sensing is acheived by measuring the amount of light reflected from the surface of the tongue. This paper compares the performance of an optical-fibre-based OPG sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This supports the notion that articulatory information has the potential to be valuable to ASH. Other studies have also found evidence of this, for example see [7].…”
Section: Discussionmentioning
confidence: 81%
“…This supports the notion that articulatory information has the potential to be valuable to ASH. Other studies have also found evidence of this, for example see [7].…”
Section: Discussionmentioning
confidence: 81%